Capabilities Of The Defense Counsel While Pre-Trial Investigation Of Criminal Offenses In The Field Of Official Activities (Review article) - Kucher, Oleksii (Archives of Criminology and Forensic Sciences, 2022)
The research paper considers provisions of the current criminal procedural legislation of Ukraine, current developments in criminal procedure science, issues of participation of the defense counsel in criminal proceedings on criminal offenses in the field of official activities, in particular while collection, assessment and provision of evidence. The idea concept has been clarified: the main place in ensuring fair justice, in particular in criminal proceedings on crimes in the field of official activities, belongs to a professional defense counsel, that is, a qualified advocate who possesses professional knowledge and practical work skills. On this basis, it has been summarized that only advocacy is founded on verification of professional knowledge, compliance with the Rules of Advocate’s Ethics, disciplinary responsibility, etc.